PENGARUH VARIETAS DAN TINGKAT KEMATANGAN BUAH TERHADAP PERKECAMBAHAN DAN FISIK BENIH KOPI ARABIKA - Saefudin Saefudin; Edi Wardiana (Pusat Penelitian dan Pengembangan Perkebunan, 2013)
One characteristic in determining the differences of fruit maturity levels in coffee is based on the difference in colour of epicarp or based on the ages of fruit that is calculated starting on a days after anthesis (HSA). In general, fruits in cherry level can result better germination than green level. This experiment was conducted at Pakuwon Experimental Station, Laboratory and Greenhouse of Indonesian Industrial and Beverage Crops Research Institute, Sukabumi, beginning from April until August 2013. The objectives of this study was to analyze the effect of varieties and fruit maturation stages on germinations and physical components of Arabica coffee seeds. The split plot design with three replications was used in this study. The main plot factors were four varieties of Arabica coffee i.e. Sigarar Utang, Kartika 1, S 795, and Kartika 2. While the split plot factors were four level of fruit maturation stages defined operationally by harvest fruit in cherry level (≈249 HSA), redish-yellow level (≈241 HSA), yellow level (≈233 HSA), and yellowish-green level (≈225 HSA). The results showed that the difference in coffee varieties and fruit maturation stages affect the germination speed of Arabica coffee seed. S 795 more faster to germinate than Sigarar Utang, Kartika 1, and Kartika 2. Similarly, fruit in the cherry level, redish-yellow, and yellow more faster to germinate than fruit in the yellowih-green level. Sigarar Utang has the highest in fresh weight of fruit and seed and dry weight of seed, and the lowest in seed water content, followed by S 795, Kartika 1, and Kartika 2. The germination success not only determined by seed physical quality components but is also influenced by environmental factors.